On the 4-color theorem for signed graphs. (January 2021) - Kardoš, František; Narboni, Jonathan
Abstract: Máčajová et al. (2016) defined the chromatic number of a signed graph which coincides for all-positive signed graphs with the chromatic number of unsigned graphs. They conjectured that in this setting, for signed planar graphs four colors are always enough, generalizing thereby The Four Color Theorem. We disprove the conjecture.